2008
DOI: 10.1073/pnas.0711713105
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the insulin signaling pathway via quantitative phosphoproteomics

Abstract: The insulin signaling pathway is of pivotal importance in metabolic diseases, such as diabetes, and in cellular processes, such as aging. Insulin activates a tyrosine phosphorylation cascade that branches to create a complex network affecting multiple biological processes. To understand the full spectrum of the tyrosine phosphorylation cascade, we have defined the tyrosine-phosphoproteome of the insulin signaling pathway, using high resolution mass spectrometry in combination with phosphotyrosine immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
209
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(213 citation statements)
references
References 51 publications
4
209
0
Order By: Relevance
“…Immunoaffinity purification based on PTMs such as phosphorylation, ubiquitylation, and acetylation allows the enrichment of proteins targeted for such modification. The combination of such purification with online LC-MS/MS analysis then allows the identification of large sets of proteins with specific PTMs [3][4][5][6][7][8][9][10][11][12]. Furthermore, methods for tagging with stable isotopes, such as stable isotope labeling in cell culture (SILAC), ICAT, or iTRAQ, provide quantitative information about proteins or peptides from MS or MS/MS spectra [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoaffinity purification based on PTMs such as phosphorylation, ubiquitylation, and acetylation allows the enrichment of proteins targeted for such modification. The combination of such purification with online LC-MS/MS analysis then allows the identification of large sets of proteins with specific PTMs [3][4][5][6][7][8][9][10][11][12]. Furthermore, methods for tagging with stable isotopes, such as stable isotope labeling in cell culture (SILAC), ICAT, or iTRAQ, provide quantitative information about proteins or peptides from MS or MS/MS spectra [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, methods for tagging with stable isotopes, such as stable isotope labeling in cell culture (SILAC), ICAT, or iTRAQ, provide quantitative information about proteins or peptides from MS or MS/MS spectra [13][14][15][16]. Indeed, the application of these quantitative methods to studies of proteins phosphorylated on tyrosine has identified many new substrates of tyrosine kinases [11,12,17].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Furthermore, quantitative techniques have also been employed for quantifying post-translational modifications such as phosphorylation. 13 However, mass spectrometry is not quantitative per se. The signal strength corresponding to the individual peptide ions recorded in the mass spectrometer does not solely depend on the concentration of the peptides, but also on many other partly uncontrollable parameters such as signal suppression effects.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated the SILAC results could measure changes in protein levels in our study. The relative standard deviation (%SD) of all the proteins in different fractions showed a quantitation precision better than 15% (Supplementary information, Figure S2B) [23]. Therefore, 1.5 was chosen as the conservative threshold for a significant ratio change during TNF-α stimulation in the present study.…”
Section: Preprocessing and Validation Of The Quantitative Datamentioning
confidence: 99%